2018
DOI: 10.3389/fsufs.2018.00047
|View full text |Cite
|
Sign up to set email alerts
|

Cold Plasma Inactivation of Escherichia coli O157:H7 Biofilms

Abstract: Pathogenic bacteria associated with biofilms on foods and food contact surfaces are a challenge to inactivate with conventional sanitizers. Cold plasma is a novel nonthermal process with potential efficacy against these pathogens. Biofilms of Escherichia coli O157:H7 were grown for 24, 48, or 72 h on glass slides and exposed to atmospheric cold plasma, 23-48 kHz, for 5, 10, or 15 s. Distance from emitter to biofilms was 5 or 7.5 cm. The temperature of the process was established using infrared digital imagery.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 28 publications
(42 reference statements)
1
17
0
Order By: Relevance
“…However, the distance from the plasma source can affect the antimicrobial effectiveness due to changes in the mass transport of the different reactive species from the discharge layer to the target surface. Comparably to this study, Katsigiannis et al and Niemira et al reported a negative correlation between the distance from the plasma source and the inactivation rate on SS inoculation [3,38]. However, Yong et al achieved an optimum inactivation at 20 mm of spacing compared to 10 and 30 mm using a pressure plasma jet on raw chicken breast and a mixture of N 2 + O 2 as working gas [39].…”
Section: Inactivation Of Salmonella and Listeria Monocytogenessupporting
confidence: 51%
“…However, the distance from the plasma source can affect the antimicrobial effectiveness due to changes in the mass transport of the different reactive species from the discharge layer to the target surface. Comparably to this study, Katsigiannis et al and Niemira et al reported a negative correlation between the distance from the plasma source and the inactivation rate on SS inoculation [3,38]. However, Yong et al achieved an optimum inactivation at 20 mm of spacing compared to 10 and 30 mm using a pressure plasma jet on raw chicken breast and a mixture of N 2 + O 2 as working gas [39].…”
Section: Inactivation Of Salmonella and Listeria Monocytogenessupporting
confidence: 51%
“…In previous studies, Cold Atmospheric Plasma (CAP) has been investigated as a novel method for inactivation of biofilms (e.g., Vleugels et al, 2005; Niemira et al, 2014, 2018; Ziuzina et al, 2015; Govaert et al, 2018a, 2019). Plasma is a partially or wholly ionized gas which consists of a large variety of (reactive) species, including ions (positive and negative), photons, free electrons, and activated neutral species (excited and radical) (Tendero et al, 2006; Kudra and Mujumdar, 2009; Banu et al, 2012; Fernández and Thompson, 2012; Lu et al, 2013; Bourke et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Figure a,b,e shows that the number of residual E. coli bacteria in the sour cherry juice is a function of plasma exposure time, so that with increasing plasma exposure time, the number of damaged and destroyed bacteria increases (Fröhling et al, ; Niemira et al, ; Segura‐Ponce et al, ; Ziuzina, Patil, Cullen, Keener, & Bourke, ). In such a way, increasing plasma exposure time from 1 to 9 min resulted in a reduction of 75% of bacteria.…”
Section: Resultsmentioning
confidence: 99%
“…Cold plasma can affect a wide range of microorganisms so that the use of this method has been widely considered (Shi et al, 2011). Several studies have been conducted on the use of APCP to reduce bacteria in solids, including freshly cut apple skin (Segura-Ponce, Reyes, Troncoso-Contreras, & Valenzuela-Tapia, 2018), biofilms infected with Escherichia coli (Niemira, Boyd, & Sites, 2018), eggshell (Harouni & Abbasi, 2013;Ragni et al, 2010), chicken skin and muscle (Noriega, Shama, Laca, Díaz, & Kong, 2011), and cheese pieces (Song et al, 2009).…”
mentioning
confidence: 99%